THE INFLUENCE OF EFFICIENCY AND CONVENIENCE ON CUSTOMER INTEREST IN MAKING TRANSACTIONS USING MOBILE BANKING AT PT.BANK SULSELBAR SIDRAP BRANCH - Rekayanti, Enny; Salida, Amrizal; Basri, Jumriah (Jurnal Manajemen Dan Bisnis, 2025)
The aim of this research is to determine the effect of efficiency an convenience on customer interest in making transactions using mobile banking at bank sulselbar sidrap branch. World development is increasingly rapid and modern both in terms of product variety, service quality and technology. Technology can be felt in various areas of life such as education and finance. The Bank has utilized the development of information technology in its banking services by launching information technology-based transaction service media, namely, mobile banking (M-Banking). The use of mobile banking services on cell phones makes it easier for customers to carry out their banking activities without time and space limitations.The research method used is a quantitative method and the type of research used is associative research which only tests the effect of efficiency and convenience on customer interest in making transactions using mobile banking. In this study, the population taken was customers of the Sidrap branch of Bank Sulselbar who had an interest in mobile banking services and who used Sulselbar mobile services. The data source in this research used a questionnaire with 101 respondents. efficiency variable (X1) and the convenience variable (X2) can simultaneously be seen that the calculated F value is 118.987 > t table value 3.09 and the significance value is 0.000 < 0.05. Because the calculated F value is much greater than the F table value and is positive and the significance value is smaller than 0.05, it can be concluded that together Efficiency (X1) and Convenience (X2) have a positive and significant influence on Customer Interest (Y) in transactions using M-Banking at Bank Sulselbar Sidenreng Rappang Branch.